A Rare Pediatric Tumor: Supratentorial High-Grade Astroblastoma Presenting as a huge Mass - Deniz Sürmeli; Boran Urfalı; Tümay Özgür (Indian Journal of Neurosurgery, 2024)
Background Astroblastoma is a rare neuroepithelial tumor of unknown origin, usually seen in children and young adults. It is usually localized to the cerebral hemisphere. Computed tomography and magnetic resonance imaging show a well-demarcated, contrast-enhancing mass with a cystic area. Characteristic histological findings are perivascular pseudorosette formation and frequent vascular hyalinization. The presented case is a 3.7-month-old female patient diagnosed with high-grade astroblastoma.